Local Surface Modifications Investigated by Combining Scanning Electrochemical Microscopy and Surface‐Enhanced Raman Scattering. Issue 5 (17th April 2018) - Clausmeyer, Jan; Nebel, Michaela; Grützke, Stefanie; Kayran, Yasin U.; Schuhmann, Wolfgang
Abstract: Scanning electrochemical microscopy (SECM) is coupled with surface‐enhanced Raman scattering (SERS) microscopy to characterize local surface modifications. SECM is utilized for the surface patterning of para ‐nitrothiophenol self‐assembled monolayers (SAMs) in the direct mode of SECM with a subsequent readout of the chemical patterns by means of combined SECM‐SERS. The SECM‐SERS combination allows monitoring of local electrochemical processes and provides simultaneous complementary spectroscopic information. The reaction products upon SAM reduction, specifically p ‐aminothiophenol groups, are distinguished from the pristine SAM and locally ruptured areas. Abstract : Simultaneous characterization : Spatially resolved electrochemistry and surface‐enhanced Raman microscopy are combined to identify chemical modification states of a self‐assembled monolayer on SERS‐active gold substrates (see figure).